xOOHDM: Integrated development environment for creating and executing models in Web applications design - Glória, João Paulo Barbosa; de Medeiros, Adriana Pereira (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
Web applications have several characteristics that differentiate them from conventional applications. However, they are often developed without considering such characteristics, even though there are specific methods for the design of these applications. This work proposes the combined use of the OOHDM method and executable models in an integrated environment for the model-driven development of Web applications. This environment provides a DSML for navigation modeling using the notations of the OOHDM and automatically generates the corresponding executable model, which permits simulating and testing this navigation without the need of code generation. It allows developers addressing specific aspects of web applications, such as hypertext, and identifying and fixing design problems beforehand via model execution.